МЕТОДИ КЕРУВАННЯ ЗАДЛЯ УСУНЕННЯ ГАРМОНІК У СИСТЕМАХ ГЕНЕРУВАННЯ ЕЛЕКТРОЕНЕРГІЇ НА ОСНОВІ МАШИНИ ПОДВІЙНОГО ЖИВЛЕННЯ - Шаповал, І.А.; Михальський, В.М.; Артеменко, М.Ю.; Чопик, В.В.; Поліщук, С.Й. (Інститут електродинаміки Національної академії наук України, 2022)
The variable speed power generation system based on a doubly-fed induction generator is the most popular in the wind industry. The stator is connected directly to the mains in such a generator, while the rotor is connected to the mains via a semiconductor converter. Low electric power quality increases energy and economic losses, leading to operational problems of production. Many publications discuss improving the electric power quality, particularly methods for eliminating harmonics for a power generation system based on a doubly-fed induction generator. Critical evaluation is needed to choose a method of eliminating harmonies for a particular case. The article presents an overview of different control methods for harmonic elimination in power generation systems based on a doubly-fed induction generator. Various strategies are used, which are used both in autonomous systems and in the mode of connection to the network. During the review of control methods for harmonic elimination, their different characteristics were noted, and the advantages and disadvantages of each method were considered. Ref. 53, fig. 6.